Hiding no scars - Mhlongo, Sanele (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a collection of free-verse narrative and prose poetry focusing on rural life and people, as well as my personal relationships. Poetry through its play with language has the ability to say things with immediacy and allows unnoticed things to acquire relevance. It gives me a framework within which to express difficult themes such as family relationships, death, solitude, and poverty. In writing these poems I have drawn on the work of Constantine P. Cavafy, particularly the poems 'Ithaka', 'The City' and 'As Much As You Can' which showcase his consistently simple narrative style that covers profound subjects. I have also been influenced by Paul Celan's poetry in his collection Breathturn Into Timestead where poems such as 'Corona', 'In praise of remoteness' and 'Twelve Years' demonstrate how poetry can have pace through tightly controlled yet experimental structure. I have also drawn on Anna Akhmatova's symbolic poetry, specifically the poems 'Now the pillow's', 'He loved three things, alive' and 'Prologue' from the selection Anna Akhmatova: Selected Poems which has its intention the re-creation of the past in the present.
Keywords: Creative writing (Higher education) -- South Africa; South African poetry (English) 21st century; Interpersonal relations in literature; Diaries -- Authorship; South African essays (English) 21st century; Russian poetry 20th century History and criticism; South African fiction (English) 21st century History and criticism; Greek poetry History and criticism; German poetry 20th century History and criticism